2015
DOI: 10.1007/s00024-015-1114-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of Efficiency and Possibility of Earthquake Predictions with Gravity Field Variation and its Analytic Signal in Western China

Abstract: This paper aimed at assessing gravity variations as precursors for earthquake prediction in the Tibet (Xizang)-QinghaiXinjiang-Sichuan Region, western China. We here take a statistical approach to evaluate efficiency and possibility of earthquake prediction. We used the most recent spatiotemporal gravity field variation datasets of 2002-2008 for the region that were provided by the Crustal Movement Observation Network of China (CMONC). The datasets were space sparse and time discrete. In 2007-2010, 13 earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Zhuang et al [61,62] used this model and a similar discrete version to model the explanatory effect of the observed data from the ultra-low frequency components of underground electric signals at 4 stations in the vicinity of Beijing in forecasting the occurrence of events with M ≥ 4 within a 300 km circle centred on Beijing, and showed that the explanatory effect is highly significant. The probability gain is about 2 -10, similar to the values obtained by Wang et al [48], Chen et al [5], and Han et al [14].…”
Section: Testing Of Earthquake Precursors and Probability Gainsupporting
confidence: 89%
See 3 more Smart Citations
“…Zhuang et al [61,62] used this model and a similar discrete version to model the explanatory effect of the observed data from the ultra-low frequency components of underground electric signals at 4 stations in the vicinity of Beijing in forecasting the occurrence of events with M ≥ 4 within a 300 km circle centred on Beijing, and showed that the explanatory effect is highly significant. The probability gain is about 2 -10, similar to the values obtained by Wang et al [48], Chen et al [5], and Han et al [14].…”
Section: Testing Of Earthquake Precursors and Probability Gainsupporting
confidence: 89%
“…For example, the crustal strain estimated from surface displacement data is closely related to the crustal stress change. Changes in the gravity field provide us with information about the vertical motion of the crustal medium (e.g., [5]). There are also many reports on the radiative signals related to the changes in geo-electromagnetic fields, coseismically (e.g., [16,17,36,37]) or preseismically (e.g., [7,11,12,14,61]).…”
Section: Determining the Critical Zonementioning
confidence: 99%
See 2 more Smart Citations
“…Automatic instrumental measurements of a variety of parameters, using advanced technology [68] were carried out. At present the Chinese monitoring network for the monitoring of earthquake precursors include GPS stations, magnetotelluric stations [69,70], and microgravimetric stations [71,72]. In particular, a network for groundwaters and gas monitoring was also set up in China.…”
Section: Chinamentioning
confidence: 99%